Meta Analisis Efektivitas Pendekatan Ekonomi dalam Program Rehabilitasi Hutan - Yurike, Yurike; Syafruddin, Yudha Saktian (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2025)
Determining the economic value of forest rehabilitation activities is important to provide the real value of the resource based on the community's perspective. Meta-analysis of the effectiveness of the economic value approach in forest rehabilitation programs is a systematic review that aims to collect and analyze data from various studies that have been conducted regarding the effectiveness of the economic approach in forest rehabilitation programs. Based on the results of the study, it shows that forest resource economics has a very fundamental position in forest management, without consideration or economic analysis, forest management efficiency is difficult to achieve. Evaluations of forest and land rehabilitation that have been carried out to date are still focused on activity accountability, only using measurements of the percentage of plant life, tree height, and level of health of plants resulting from forest and land rehabilitation, which is not enough to evaluate the total success rate of forest rehabilitation. The need to consider economic aspects as part of the design and strategy of forest rehabilitation projects.